2001
DOI: 10.1074/jbc.m104793200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Mouse δ-Opioid Receptor Gene

Abstract: Previously, we identified a minimum core promoter of the mouse ␦-opioid receptor (DOR) gene. The DOR promoter contains an E-box that binds upstream stimulatory factor and is crucial for the DOR promoter activity in NS20Y cells, a mouse neuronal cell line that constitutively expresses DOR. In the present study, we further analyzed the DOR promoter in NS20Y cells and have demonstrated that transcription factor Ets-1 binds to an Ets-1-binding site overlapping the E-box and trans-activates the DOR promoter by syne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…An attractive biological feature of USF and Sp proteins involves their abilities to mediate a wide range of transcriptional activities via protein-protein interactions with other families of transcription factors including Ets-1 (30,31), MTF-1 (32), hepatic nuclear factor-4 (33), and the basal transcription factors TFIID (34,35) and TFII-I (36,37). In the dCK promoter, the GC-box elements and the E-box elements are juxtaposed.…”
Section: Discussionmentioning
confidence: 99%
“…An attractive biological feature of USF and Sp proteins involves their abilities to mediate a wide range of transcriptional activities via protein-protein interactions with other families of transcription factors including Ets-1 (30,31), MTF-1 (32), hepatic nuclear factor-4 (33), and the basal transcription factors TFIID (34,35) and TFII-I (36,37). In the dCK promoter, the GC-box elements and the E-box elements are juxtaposed.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, the CGRP 18-bp enhancer is controlled by USF and the cell-specific FoxA2 protein in thyroid C-cell lines (12). Similar partnerships with other factors have been reported for USF (41,47), including in the nervous system (48,49). Although we cannot rule out an unknown accessory factor or co-activator, the FoxA2 protein is not a candidate because mutation of the FoxA2 site did not decrease reporter activity in cultured neurons (27), and neither FoxA2 RNA nor protein could be detected in rat trigeminal ganglia by RT-PCR or Western blots (data not shown).…”
Section: Discussionmentioning
confidence: 58%
“…In view of this, the fact that the mDOR gene is expressed in a tissue-and cell type-specific manner is rather surprising, because the housekeeping genes are usually ubiquitously expressed. Previous studies demonstrated that the mDOR promoter region from Ϫ262 to Ϫ141 containing Sp1/ Sp3, upstream stimulatory factor, and Ets-1-binding sites is critical for its basal promoter activity (5,6). Given that these transcriptional factors are also ubiquitously expressed, the mechanisms involved in the regulation of cell type-specific expression of mDOR are not clear.…”
Section: Discussionmentioning
confidence: 97%
“…Several transcription factors have been shown to bind to the mDOR promoter region and play a critical role in the regulation of mDOR promoter activity ( Fig. 2A) (5,6). Among these transcription factors, Sp1/Sp3 accounts for about 70% of the promoter activity in a transient transfection assay (5).…”
Section: Involvement Of Sp3 In the Mecp1-like Complex Formed By Me-26mentioning
confidence: 99%
See 1 more Smart Citation